ARBITRASE DALAM SENGKETA HAK ASUH ANAK DI INDONESIA: SOLUSI BERBASIS KEADILAN DAN KEPENTINGAN ANAK - Kasnan (Sekolah Tinggi Islam Syariah (STIS) Al-Ittihad Bima, 2025)
Child custody disputes are complex issues in family law that often involve emotional and procedural conflicts between parents. In the Indonesian context, traditional litigation often lacks attention to the principle of the best interests of the child, as stipulated in Law No. 23/2002 on Child Protection. This study aims to analyze the urgency of implementing arbitration as an alternative to child custody dispute resolution. Using a normative legal approach, this study evaluates regulations related to arbitration, the principles of justice, and the best interests of the child, and compares similar practices in various countries. The data is analyzed qualitatively through legal inventory and synchronization between regulations. The results show that arbitration offers a more flexible, efficient and child welfare-oriented solution compared to litigation. Arbitration allows for faster decision-making, maintains the privacy of the parties involved, and provides space for the participation of the child